Integrating Mind Body Soul Perspectives in Education: Insights from Neuroscience and Traditional Healing Practices - Rodríguez, Sofia Martínez (BIRCU, 2012)
Pain remains one of the most pervasive health challenges worldwide, affecting millions of individuals and contributing significantly to disability and diminished quality of life. While biomedical research has produced substantial advancements in understanding physiological mechanisms of pain, purely biological models often fail to fully explain the complexity of chronic pain experiences. Increasingly, scholars and clinicians recognize that pain involves not only physical processes but also psychological, social, and spiritual dimensions. This article explores the convergence between modern pain neuroscience and ancient holistic healing traditions, arguing that a multidimensional understanding of pain is necessary for effective treatment and patient wellbeing. Drawing upon interdisciplinary literature from neuroscience, medical history, psychology, and cross-cultural healing systems, this study examines how contemporary scientific discoveries align with long-standing principles in traditional medical systems such as those articulated by Avicenna, Traditional Chinese Medicine, Ayurveda, and Indigenous healing traditions. The analysis highlights key developments in modern pain theory, including the Gate Control Theory and the Neuromatrix model, which emphasize the role of brain networks integrating cognitive and emotional factors in pain perception. Evidence from neuroimaging and clinical studies demonstrates that psychological states and spiritual beliefs can significantly modulate pain experiences through specific neural mechanisms. These findings support the integration of biopsychosocial-spiritual frameworks into modern healthcare. The study concludes that effective pain management requires holistic approaches addressing biological, psychological, social, and spiritual factors simultaneously. Integrative healthcare models may therefore offer more comprehensive and compassionate strategies for addressing chronic pain.